Implementation of Scientific Creativity Project-Based Learning in Increasing Students' Scientific Creativity with An In-Depth Learning Approach - Wasirotuz Zahroh; Maimun Sumo; Moch Haikal (FKIP - Universitas Riau, 2026)
This study aims to analyze research trends regarding the implementation of Scientific Creativity Project-Based Learning to enhance students' scientific creativity through a deep learning approach. The study employs a Systematic Literature Review (SLR) method following PRISMA procedures, supported by bibliometric analysis using VOSviewer. Data were derived from 50 scientific articles published between 2020 and 2025. Articles were selected based on topic relevance, publication type (scientific journal articles), English language usage, full-text availability, and the inclusion of junior high, senior high, and university students. Articles failing to meet these criteria were excluded from the analysis. The results indicate an increase in the number of publications from 5 articles in 2020 to 11 articles in 2025. VOSviewer analysis identified 91 keywords categorized into three main clusters, demonstrating the interconnections among project-based learning, scientific creativity, and deep learning. Overlay visualization reveals a shift in research focus from technology and technical aspects toward instructional implementation and the development of student creativity, while density visualization highlights the dominance of topics related to deep learning and technology. These findings suggest that integrating project-based learning, scientific creativity, and deep learning has the potential to foster more meaningful learning and enhance students' scientific creativity.